Pelatihan Pembuatan Packaging dalam Upaya Peningkatan Produk - Asdilvira, Bebi (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
The household-scale food industry in Medan City has great potential but is often constrained by the low visual competitiveness of its products. The main problem faced is the use of conventional packaging which is minimal in information and unattractive, making it difficult to compete in the modern market. This community service activity aims to improve the knowledge and skills of